PENGARUH STRUKTUR KEPEMILIKAN TERHADAP PENGHINDARAN PAJAK DENGAN DIREKTUR PEREMPUAN SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Khalida Darma Septia Sihombing; Wahyu Meiranto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of ownership structure on tax avoidance and the role of female directors in moderating this relationship in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This study is grounded in agency theory.The population used in this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Purposive sampling was used in selecting the research sample, resulting in 309 research samples for three consecutive years (2022–2024).The results of the analysis indicate that family ownership, managerial ownership, foreign ownership, and female directors do not have a significant effect on tax avoidance. Meanwhile, institutional ownership has a negative and significant effect on tax avoidance. Furthermore, female directors only moderate the relationship between managerial ownership and tax avoidance, while they do not moderate the relationship between family ownership, institutional ownership, and foreign ownership on tax avoidance.